2015
DOI: 10.1038/srep13890
|View full text |Cite
|
Sign up to set email alerts
|

High content analysis at single cell level identifies different cellular responses dependent on nanomaterial concentrations

Abstract: A mechanistic understanding of nanomaterial (NM) interaction with biological environments is pivotal for the safe transition from basic science to applied nanomedicine. NM exposure results in varying levels of internalized NM in different neighboring cells, due to variances in cell size, cell cycle phase and NM agglomeration. Using high-content analysis, we investigated the cytotoxic effects of fluorescent quantum dots on cultured cells, where all effects were correlated with the concentration of NMs at the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 50 publications
1
31
1
Order By: Relevance
“…To evaluate the toxicity of these NPs, a validated high content imaging approach was used, which enables the generation of large datasets generated over the entire of predefined part of the cell population. Data are then generated to the level of the single cell, after which the mean and distribution of the data can be calculated to determine whether the parameter studied is normally distributed or whether the value derived is heavily influenced by outliers . This allows for a more detailed understanding of cell–NP interactions in comparison to classical biochemical assays where a single value is given as an average for the entire population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the toxicity of these NPs, a validated high content imaging approach was used, which enables the generation of large datasets generated over the entire of predefined part of the cell population. Data are then generated to the level of the single cell, after which the mean and distribution of the data can be calculated to determine whether the parameter studied is normally distributed or whether the value derived is heavily influenced by outliers . This allows for a more detailed understanding of cell–NP interactions in comparison to classical biochemical assays where a single value is given as an average for the entire population.…”
Section: Resultsmentioning
confidence: 99%
“…Every condition was performed in triplicate and results were analyzed based on the three repeats. The high‐content imaging experiments were then performed based on previously validated methods …”
Section: Methodsmentioning
confidence: 99%
“…The measured biomarker assays in the present study indicated that the MWCNT effects were dose-dependent [52]. indication of loss in compensatory mechanisms that curb the effects of reactive oxygen species (ROS) [53,54].…”
Section: Discussionmentioning
confidence: 89%
“…Following previously described protocols, [13] the following cellular parameters were analyzed: autophagy (LC3), cell area (A), endosome size (S E ), membrane damage (MD), mitochondrial health (MH), reactive oxidative species (ROS), cell skewness (SK), cell viability (V), and focal adhesion (FA). Following previously described protocols, [13] the following cellular parameters were analyzed: autophagy (LC3), cell area (A), endosome size (S E ), membrane damage (MD), mitochondrial health (MH), reactive oxidative species (ROS), cell skewness (SK), cell viability (V), and focal adhesion (FA).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thet wo series of fluorescently labeled NPs (2 4 samples) were incubated with two cell lines,m urine C17.2 neural progenitor and primary human umbilical vein endothelial cells (HUVECs). Following previously described protocols, [13] the following cellular parameters were analyzed: autophagy (LC3), cell area (A), endosome size (S E ), membrane damage (MD), mitochondrial health (MH), reactive oxidative species (ROS), cell skewness (SK), cell viability (V), and focal adhesion (FA). Forc ellular exposure studies,c ells were incubated with the NPs at an equal number of NPs (1.25, 2.5, or 5nm)o ra te qual mass of gold (62.5, 125, or 250 mgmL À1 ;s ee the Supporting Information).…”
Section: Angewandte Chemiementioning
confidence: 99%